The electrocatalysis of oxygen evolution reaction on La1−xCaxFeO3−δ perovskites in alkaline solution. (1st March 2018) - Sankannavar, Ravi; Sarkar, A.
Abstract: The electrocatalytic oxygen evolution reaction (OER) on iron based perovskites with composition La1− x Ca x FeO3− δ (0.0 ≤ x ≤ 1.0) in alkaline solution has been investigated. The perovskite samples were synthesized by combustion method. Energy dispersive spectroscopy and X-ray photoelectron spectroscopy were used to determine the bulk and the surface composition, respectively. The X-ray diffraction and iodometric titration method were employed to examine the phases and the oxidation state, respectively. It was observed that incorporation of calcium (Ca 2+ ) ions in the lattice of LaFeO3 decreases the lattice parameters and the cell volume systematically as evaluated by Rietveld method. Furthermore, increase in the degree of Ca 2+ substitution from 0.0 to 1.0, increases the average oxidation state of iron from Fe 3+ to Fe 4+ in addition to creating oxygen vacancies. The evaluation of OER kinetics on a rotating disk electrode setup suggests that incorporation of Ca 2+ decreases the activity initially (0.0 ≤ x ≤ 0.4), but further substitution increases the activity. The maximum activity was observed for x = 1.0. This change in the OER activity suggests an interplay between the bond lengths and angles, oxygen vacancy and the average oxidation state of Fe. Highlights: Ca 2+ substituted La1− x Ca x FeO3− δ perovskites were used for OER in alkaline media. Ca 2+ substitution increased average oxidation state of Fe and created O2 vacancies. Smaller ionic radius of Fe 4+ contracts the lattice. Ca 2+ substitution decreases Tafel slope as well as exchange current density.